Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada Perawat RS PKU Muhammadiyah Gamping - Melinda Kartikaningrum; Nany Noor Kurniyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of Work Motivation (X1) and Work Environment (X2) on Employee Performance (Y). This is a quantitative study. The population in this research consists of nurses at RS PKU Muhammadiyah Gamping, with a sample of 72 respondents. Data collection was conducted using a questionnaire with a Likert scale. The data analysis methods used include classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, and hypothesis testing (t-test, F-test, and R² test). The analysis results show the significance level of Work Motivation (X1) and Work Environment and whether they have an effect on Employee Performance. Based on the t-test results: (1) The effect of Work Motivation (X1) shows a value of 2.071 with a significance of 0.042 < 0.05, indicating that Work Motivation (X1) has a significant effect on Employee Performance (Y) at RS PKU Muhammadiyah Gamping. (2) The effect of Work Environment (X2) shows a value of 4.766 with a significance of 0.000 < 0.05, indicating that the Work Environment (X2) has a significant effect on Employee Performance (Y). The F-test results show that Work Motivation (X1) and Work Environment (X2) together significantly affect Employee Performance (Y), with an F-value of 38.247 and a significance level of 0.000 < 0.05, indicating a simultaneous significant effect on Employee Performance (Y) among nurses at RS PKU Muhammadiyah Gamping.